Métodos de colapsagem de variantes raras para mapeamento de QTLs - João, Lara Midena (Universidade Federal de São Carlos, 2024)
The mapping of regions in the genome associated with quantitative traits (QTLs) through SNP-type genetic markers has been one of the central problems in Genetics and Molecular Biology and several methods of detection and identification of QTLs have been proposed in the literature. In this work, we research, study and describe the main methods that have been used for this purpose in independent data with the presence of rare variants. We also highlight its advantages and disadvantages and list the algorithms that are already implemented and available for use. The performance of the different methodologies studied was compared via GAW 17 data analysis.
Rare variant collapsing methods for QTLs mapping
Keywords: Dados independentes; GAW 17; Variantes raras; Independent data; Rare variants; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA::REGRESSAO E CORRELACAO